PCB contamination in surface sediments in the coastal waters of Costa Rica - Spongberg, Alison L. (2004)
This paper describes the initial investigation of PCB concentrations in four geographical regions (three on the Pacific and one in the Caribbean) of coastal Costa Rica: Bahia Culebra, Golfo Dulce, Golfo de Nicoya, and Limón. Overall total concentrations of PCB were low in all areas except around the port of Golfito (Golfo Dulce). Overall average concentration is 2.80 ng/g dw, with a standard deviation of 2.75. The low concentration could be due to lack of contamination or the subsequent degradation in the warm climate, or the low sorptive capacity of the sediment. Further investigation is ongoing.